1991
DOI: 10.3109/03630269108998861
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization and Solubility of Recombinant Hemoglobins α2β26VAL(HB S) and α2β26LEU(HB LEU)

Abstract: In an effort to clarify the role of amino acid hydrophobicity at the beta 6 position in sickling we have made recombinant hemoglobin tetramers containing beta 6 Val (Hb S) and beta 6 Leu (Hb Leu). Recombinant Hb S and Hb Leu had the same electrophoretic mobility, chromatographic behavior, and absorption spectrum. The deoxy form of both tetramers polymerized in high phosphate buffer (1.8 M) and exhibited distinct delay times prior to polymerization. The kinetics of polymerization for recombinant and native Hb S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 19 publications
5
28
0
Order By: Relevance
“…The synthetic human a-and 3-globin genes for normal Hb (17) and for a few other mutant Hbs (18)(19)(20)(21)(22)27) have been expressed in E. coli. However, the Hb produced in this system is not processed at its N terminus in the same way that human Hb is processed in human reticulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic human a-and 3-globin genes for normal Hb (17) and for a few other mutant Hbs (18)(19)(20)(21)(22)27) have been expressed in E. coli. However, the Hb produced in this system is not processed at its N terminus in the same way that human Hb is processed in human reticulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cells from overnight growths at 30°C were lysed and treated with DNase I, and soluble proteins were removed by centnfugation [18]. After 3-5 washes with 0.5% (v/v) Triton X-100, the resultant pellet was dissolved in 8 M urea/SO mM Tris buffer and the fusion protein was purified by ion-exchange chromatography (CM-Sepharose).…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that polymerization is not specific for valine at the j36 position, and that an abrupt decrease in deoxyhemoglobin solubility may depend, in general, on hydrophobic amino acids at the 86 position. To further understand the relationship between 86 amino acid hydrophobicity and deoxyhemoglobin solubility, we compared solubilities in high phosphate buffers for #J6 Trp and Ala hemoglobins with those of 86 Glu (Hb A), Val (Hb S), Leu (aAL""), Ile (cx&"~) and Gln (Hb Machida) [17,18,21] (Table I).…”
Section: Solubility Of Hemoglobins Modijied At the 86 Positionmentioning
confidence: 99%
“…We previously engineered and isolated Hb S ␤T87Q as well as Hb F ␥E6V and Hb F ␥E6V,␥Q87T, using a yeast expression system, and characterized the polymerization properties of these variants to clarify the role of Gln at ␥87 in Hb F-mediated inhibition of deoxy Hb S polymerization (12,13). Oversaturated deoxy Hb F ␥E6V and Hb F ␥E6V,␥Q87T polymerized similarly without a delay time at a higher concentration than Hb S, even though studies of mixtures of Hb S and Hb S ␤T87Q indicated that the Thr 3 Gln difference at 87 (F3) in the non-␣-globin chain is a key amino acid required for Hb F inhibition of Hb S polymerization.…”
Section: From the Children's Hospital Of Philadelphia Division Of Hementioning
confidence: 99%